2012
DOI: 10.1002/ijc.27928
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and characterization of inflammatory breast cancer emboli grown in vitro

Abstract: Inflammatory breast cancer (IBC) is the deadliest form of breast cancer, presenting as intralymphatic emboli. Emboli within the dermal lymphatic vessels are thought to contribute to rapid metastasis. The lack of appropriate in vitro models has made it difficult to accurately study how IBC emboli metastasize. To date, attempts at creating IBC tumor emboli in vitro have used 3D culture on a solid layer of Matrigel TM , which does not resemble the physical properties of the lymphatic system. Dermal lymphatic flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 56 publications
3
67
0
Order By: Relevance
“…These cells have the ability to spontaneously form 3D tumor spheroids when seeded in ultra-low attachment plates similar to previous studies [19, 27, 30]. Representative images of SUM149 tumor spheroids are shown in in Figure 2A.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These cells have the ability to spontaneously form 3D tumor spheroids when seeded in ultra-low attachment plates similar to previous studies [19, 27, 30]. Representative images of SUM149 tumor spheroids are shown in in Figure 2A.…”
Section: Resultssupporting
confidence: 81%
“…To study this, we used a recently reported method [27] wherein IBC cells are cultured in media supplemented with PEG-8000 and grown on an orbital shaker, simulating the viscosity and shear force of the lymphatic system. These conditions allow IBC cells to form tight tumor cell clusters with similar phenotype and histological aspects observed in tumor emboli found in patient samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBC is marked by the presence of dermal and stromal tumor emboli in breast tissue, a hallmark of the disease. Upon obstructing lymphatic vessels, tumor emboli prevent proper drainage of the lymph fluid, causing skin reddening and painful swelling of breast tissue (Vermeulen et al , 2010; Lehman et al , 2013). IBC cells display high ALDH positivity, express high levels of E-cadherin, and interestingly, continue to express elevated levels of epithelial cell markers like E-cadherin, while gaining mesenchymal and stem-like characteristics (Nguyen et al , 2006; Charafe-jauffret et al , 2010; Cohen et al , 2015).…”
Section: Various 3d Culture Models Of Tumormentioning
confidence: 99%
“…Serum free media is added to the bottom chamber and media supplemented with growth factors that act as a chemoattractant is added to the top chamber. Within few hours cells begin to disseminate from the spheroid, proteolytically cleave through the matrix and migrate towards the upper chamber (Lehman et al , 2013). The invasive potential of cells through cellular barrier can be evaluated by further modifying the assay where endothelial cells are plated atop the porous membrane.…”
Section: Applications Of Tumor Spheroids In Cancer Researchmentioning
confidence: 99%